Associations between early life stress and anterior pituitary gland volume development during late childhood. (December 2020) - Farrow, Paige; Simmons, Julian G.; Pozzi, Elena; Díaz-Arteche, Carmela; Richmond, Sally; Bray, Katherine; Schwartz, Orli; Whittle, Sarah
Highlights: Early life stress thought to disrupt brain development. Childhood neglect linked with size of the anterior pituitary gland volume. Childhood neglect linked with larger pituitary gland across time (age 8 and 10 years). Other stress variables not associated with pituitary gland development. Findings may suggest neglect associated with changes in HPA axis function. Abstract: Early Life Stress (ELS) is thought to influence Hypothalamic-Pituitary-Adrenal-Axis (HPAA) functioning, contributing to an increased risk for psychopathology through dysregulation of biological stress responses. Research exploring relationships between ELS and HPAA functioning has largely focused on its key hormonal output, cortisol. However, findings have been inconsistent, potentially due to cortisol's distinctive diurnal patterns and dynamic nature complicating its accurate measurement. Thus, this study explored the link between ELS and a more stable, structural component of the HPAA, specifically, anterior pituitary gland volume (PGV) in a community sample of children ( N = 129, 68 female). PGV was traced from Magnetic Resonance Imaging brain scans across two time-points at ages 8 (baseline) and 10 years (follow-up). ELS exposure was assessed at baseline through parent-report questionnaires and maternal affective behavior observed in mother-child interaction tasks. ELS variables were reduced to a 5-factor structure using exploratory factor analysis – Uninvolved Parenting, Negative Affective Parenting, Neglect, Trauma, and Dysfunctional Discipline. Direct and sex-moderated associations between ELS and PGV were explored using regression and linear mixed models analyses. PGV-mediated associations between ELS and internalizing symptoms were also investigated. Childhood Neglect was significantly associated with greater baseline anterior PGV, that was stable over the follow-up period. This effect was found in the whole sample, and in males, specifically. No mediation effects were found. Results suggest that neglect may play a unique role in HPAA neurodevelopment; however, it is important that future research extends into adolescence to more clearly characterize these neurodevelopmental associations and any subsequent psychopathological outcomes.